Upaya Pencegahan Kekerasan Seksual dan Intoleransi Melalui Kegiatan Sosialisasi di SD Negeri 1 Astana - Dianasari Dianasari; Ismi Safitri Indriyani; Kusila Kusila; Nunung Sunari; Syifaul Jannah; Indah Noviyanti (Mathematics Education Study Program, 2025)
The three cardinal sins of education are serious issues that include bullying, sexual violence and intolerance. These three things are a big challenge in the world of education in Indonesia, because they can damage morale, integrity, and the comfort of the learning environment. Bullying often occurs without the perpetrators or victims realising it, sexual violence can destroy the mentality of students, while intolerance fosters hatred and destroys social harmony. Based on observations made at SDN 1 Astana, it was found that one of the main problems was the practice of bullying among students. Many students unconsciously commit acts of bullying, both verbally and physically, against their own friends. This phenomenon shows that awareness of the negative impact of bullying is still low among students. To raise students' awareness of the three cardinal sins of education. One of the proposed solutions is the implementation of the “Mini Cinema” programme, which is an educational short film screening activity that specifically highlights the adverse effects of bullying, sexual violence and intolerance. The programme is designed to be an engaging and educational socialisation medium, while building empathy among students. With this approach, it is hoped that students at SDN 1 Astana can understand the importance of respecting and supporting one another, creating a safer, more inclusive school environment free from the threat of violence.